(untitled) (Islamic Sciences Journal, 2023)
Thank God, The First that nothing is before him, The Last that nothing is after him, The Manifest that nothing is above him, The Hidden that nothing is underneath him, The All-Hearing who hears the noise of the sounds of different languages without being distracted by the different sounds, and The All-seeing who sees the black ant crawling on the black rock in the dark of night. And peace and blessings be upon our Prophet Muhammad and upon his family and Companions. Seeking the help of the jinn is a very serious issue and it is still a matter of a great caution and a great fear among the righteous scholars; because it was the cause of the worst kinds of disbelief, injustice and debauchery -may Allah protect us and all Muslims- God has made barriers between the two weights (human, jinn), fears, and differences between the two natures, so that they worship their Lord as prescribed to them, without the help of the other, except within a very limited cases, and with a precise controls that only well known by the scholars for fear that evil happens, but the devils of the jinn and the human have disobeyed God, and they have said and done what is not prescribed to them, and Satan was keen on this as its one of his greatest ways of misguidance. As the devils of jinn dominated the human being in our time, I liked to have my research entitled [Verdict of Seeking Help form Jinn] to clarify the issue and its ruling in Islam, and I divided the research into an introduction and six topics. First Topic: Definition of Seeking Help from Jinn and its Verity. Second Topic: Sections of Seeking Help from Jinn. Third Topic: What Are Jinn? The Reality of Jinn? 1. The Definition of Jinn. 2. The Different Cases of Jinn. Fourth Topic: Seeking Help from Jinn and its Forms. Fifth Topic: Those Who Say that it is Permissible to Use Jinn in Permissible Conditions and Mention their Restrictions. Sixth Topic: Those Who Say that it is not Permissible to Use Jinn and Their Evidences.